Effect of mist/steam uniformity on heat transfer characteristics in unconfined jet impingement - Alhajeri, Hamad M.; Almutairi, Abdulrahman; Alenezi, Abdulrahman H.; Gamil, Abdelaziz A. A.; Al-Hajeri, M. H. (Elsevier, 2020)
This paper presents the numerical investigations of the injection of mist into an unconfined cooling steam jet to analyze the effects on the corresponding heat transfer characteristics. The infusion of mist into an confined cooling steam jet demonstrates a remarkable improvement in the heat transfer specifications as described in numerous previous studies. Therefore, the current research contributes to the knowledge by focusing on the uniformity configurations of the injected second phase to the unconfined regions and the influence of the surrounding environment on the mist injected. Several variables govern the physical model of the mist concentration and jet to plate distance, which is included in three-dimensional incompressible Navier-Stokes flow with the discrete phase model for the multiphase flow regime. The simulation was conducted over a range of common working Reynolds numbers. The results show that controlling the uniformity of the injected mist will redefine the cooling characteristics. The accumulated mist near the edge leads to the heat transfer enhancement at H/D = 2, 4, and 6. The surrounding environment had a significant influence on the droplet behavior at H/D = 8, thus causing a heat transfer reduction of 8%. The droplet Stock number can determine the droplet performance on the target wall and introducing mist generates a third heat transfer peak that results in an average increase of 38% for 1% mist.
Keywords: Heat transfer; Unconfined jet impingement; Mist-steam mixture; Droplet uniformity